MALAYSIAN TERRORIST ORGANIZATIONS AND POTENTIAL INVOLVEMENT IN CRIMINAL ACTIVITIES - Aslam, Mohd Mizan Mohammad (Journal of Al-Tamaddun, 2020)
Homegrown terrorist organizations such as Kumpulan Militant Malaysia (KMM), Jemaah Islamiyyah (JI), Darul Islam Sabah (DIS), Al Qaeda and Islamic State (IS) or DAESH have created their own “domestic” criminal capabilities. The series of bombings and terrorist attacks which the terrorists have been known to carry out in this region cannot be done without a sturdy source of funding. Either small or big scale terror activities depends on funding, because terrorist operators and suicide bombers also need money for a living. Proactive vigilance and law enforcement activities aimed at stopping funding for terrorist organizations have halted their movements. As a result, they have lately been forming partnership with organized and underground crime groups in order to continue to survive. This study has identified the activities of at least four main terror-crime groups operating in Malaysia known as: human trafficking, piracy, kidnaping for ransom (KFR), and smuggling. Drawing on these accounts, it is discussed in this article that the level of a terrorist group’s organizational capability is the most vital factor of the crimes they were engaged in. Significant data from the series of interview and literature review were used to produce output which would be able to help the authorities in Malaysia to have a wider understanding of the crime-terror nexus in Malaysia.